2003
DOI: 10.1088/0957-0233/14/8/337
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-point ultraviolet optical fibre sensor based on cladding luminescence

Abstract: A novel multi-point optical fibre sensor for ultraviolet detection is presented. The sensor is a single piece of large-core polymer optical fibre which has had sections of its cladding stripped and replaced with phosphor-doped epoxies. These photoluminescent coatings act as the new cladding. Two points on the fibre have been coated with a different phosphor, each providing a different emission spectrum (red and green) when stimulated by ultraviolet radiation. The spectral emission intensity is dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The former are small in size, light, electrically safe and resistant to electromagnetic interference. Moreover, it offers the possibility of distributed measurements along the whole sensor length [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The former are small in size, light, electrically safe and resistant to electromagnetic interference. Moreover, it offers the possibility of distributed measurements along the whole sensor length [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Between 1995 and 2005 not much happened in this field with the exception of the works by Prince et al 21 , Egalon 22,23 and Fitzpatrick et al 24 . Prince et al reported on a rather complicated system, made of a sensing and illumination fibers, to monitor chemical species.…”
Section: Introductionmentioning
confidence: 99%
“…Fitzpatrick et al 24 also employed the side illumination approach to address a related problem: that of detecting UV radiation. In this case, the UV rays act as the side illumination "source".…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the tip of an optical fiber is coated with a suitable luminescent material, and the emitted radiation is collected by the fiber core and transmitted to the diagnostics. While this method enables detection from the ultraviolet (UV) to the x-ray spectral regions [1][2][3][4], spatially resolved measurements are cumbersome and difficult, especially in hazardous environments. In addition, the detectable spectral range is limited by the properties of the luminescent material, and material degradation (e.g., photo-darkening) can severely limit applications when the irradiation levels are high.…”
mentioning
confidence: 99%